Application of 3D X-ray CT Scanning Techniques to Evaluate Fracture Damage Zone in Anisotropic Granitic Rock - M. H. B. Nasseri (Canadian Institute of Mining, Metallurgy and Petroleum, 2009)
Barre granite?s samples have been tested for fracture toughness under mode I along two different directions with respect to microstructural fabrics were investigated. 3D objects counter algorithm technique is applied on micro CT images to identify physical properties such as crack induced porosity, crack density, generated total surface area and contribution of individual mineral grains within the damaged zone.The result obtained justifies very well the fracture toughness anisotropy in Barre granite, and explains the difference in the structure of the damage zone evolving as a result of test crack interacting with pre-existing microstructural fabrics. The present study has potential application in the fields of rock mass stability, oil reservoir stimulation, rock fragmentation and damage in blasting and emplacement of dykes.